Study of the adhesion of explosive residues to the finger and transfer to clothing and luggage. Issue 6 (November 2018) - Lees, Heidi; Zapata, Félix; Vaher, Merike; García-Ruiz, Carmen
Abstract: It is important to understand the extent of transfer of explosive particles to different surfaces in order to better evaluate potential cross-contamination by explosives in crowded security controls such as those at airports. This work investigated the transfer of nine explosive residues (ANFO, dynamite, black powder, TNT, HMTD, PETN, NH4 NO3, KNO3, NaClO3 ) through fingerprints from one surface to another. First, the extent of adhesion of explosive residues from different surfaces to the bare finger, nitrile and latex gloves was studied. Then, the transfer of explosive residues from one surface to another through fingerprints was investigated. Cotton fabric (hereinafter referred to as cotton) as clothing material and polycarbonate plastic (hereinafter referred to as polycarbonate) as luggage material were chosen for the experiments. These surfaces containing explosive particles were imaged using a reflex camera before and after the particles were transferred. Afterwards the images were processed in MATLAB where pixels corresponding to explosive residues were quantified. Results demonstrated that transfer of explosive residues frequently occurred with certain differences among materials. Generally, the amount of explosive particles adhered to the finger decreased in the following order: skin>latex>nitrile, while the transfer of particles from the finger to another surface was the opposite. The adhesion of explosive residues from polycarbonate to the finger was found to be better compared to cotton, while the amount of particles transferred to cotton was higher. Highlights: Study of transfer of explosive residues through fingerprints. The amount of residues adhered to the finger decreased in the order skin>latex>nitrile. Transfer of residues occurred from one surface to another, despite gloves on or not. The highest amount of residues was transferred from polycarbonate to cotton surface. Cross-contamination can take place at airports through contaminated hands